Single‐cell RNA‐seq reveals altered NK cell subsets and reduced levels of cytotoxic molecules in patients with ankylosing spondylitis - Ren, Conglin; Li, Mingshuang; Zheng, Yang; Cai, Bingbing; Du, Weibin; Zhang, Helou; Wu, Fengqing; Tong, Mengsha; Lin, Fu; Wang, Jinfu; Quan, Renfu (Journal of cellular and molecular medicine, 2022)
Ankylosing spondylitis (AS) is an autoimmune disease with unknown aetiology. To unravel the mechanisms mediating AS pathogenesis, we profiled peripheral blood mononuclear cells (PBMCs) from AS patients and healthy subjects using 10X single‐cell RNA sequencing. The frequencies of immune cell subsets were evaluated by flow cytometry. NK cells were purified from PBMCs using isolation kit and were examined for gene expression by RT‐qPCR. Plasma levels of cytolytic molecules were examined by enzyme‐linked immunosorbent assay. Compared to healthy controls, AS patients showed a significant decrease in total NK cells as well as CD56dim NK subset, whereas CD56bright NK cells were increased. Additionally, impaired expression of cytotoxic genes in NK cells of AS patients was observed by bioinformatics algorithm and verified by RT‐qPCR and flow cytometry. Consistent with changes in transcriptomics, we found decreased plasma levels of granzymes, but not granulysin, in AS patients. Furthermore, Pearson correlation analysis revealed a negative correlation between plasma GZMB levels and disease activity (r = −0.5275, p = 0.0358). No correlation was observed between plasma cytolytic molecules and biochemical indexes (ESR and CRP). Our findings uncover altered NK cell subsets and cytotoxic profiles in peripheral circulation of AS patients at single‐cell resolution.